2015
DOI: 10.1007/s12519-015-0032-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of hemolytic uremic syndrome secondary to cobalamin C disorder in Chinese children

Abstract: The results of this study demonstrated that cbl-C disorder should be investigated in any child presenting with HUS. The high concentrations of homocysteine and MMA could be used for timely recognization of the disease. Once the high levels of plasma homocystein and/or plasma or urine MMA are detected, the treatment with parenteral hydroxocobalamin should be prescribed immediately. The early diagnosis and treatment would contribute to the good prognosis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“… 31 This confirms the wide heterogeneity of cblC disease, and that the diagnosis has to be evoked even in the absence of neurologic damage. 32 Likewise, only 1 patient presented with PAH in our study, but several cases of PAH during cblC deficiency have been reported, frequently associated with TMA. 33 , 34 …”
Section: Discussionmentioning
confidence: 46%
“… 31 This confirms the wide heterogeneity of cblC disease, and that the diagnosis has to be evoked even in the absence of neurologic damage. 32 Likewise, only 1 patient presented with PAH in our study, but several cases of PAH during cblC deficiency have been reported, frequently associated with TMA. 33 , 34 …”
Section: Discussionmentioning
confidence: 46%
“…We identified 36 patients ([14, 2138], including one unpublished patient) with established cblC defect and renal involvement. Diagnosis of MMACHC was confirmed biochemically in 34 patients and genetically in 18 (Table 3; for individual data, see Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The kidney excretion functions of the cblC-MMA patients were affected by high concentrations of methylmalonic acid and homocysteine. The mechanisms of renal injury of cblC-MMA patients included that homocysteine caused vascular coagulation and glomerular vascular injury ( 36 , 37 ) and methylmalonic acid induced renal tubular acidosis ( 38 , 39 ). In this study, we found the levels of urea were obviously higher than normal children, which indicated the renal injury in cblC-MMA.…”
Section: Discussionmentioning
confidence: 99%